Jacob and the divine trickster a theology of deception and YHWH's fidelity to the ancestral promise in the Jacob cycle - Anderson, John E. 1981- (Winona Lake, Ind. Eisenbrauns, 2011)
What role does God play in relation to the deceptions that pervade the Jacob cycle? What has not been investigated is the way God may factor into this deceptive activity. The book of Genesis contains a latent tension: Jacob is both a brazen trickster who deceives members of his own family and YHWH's chosen, from whom the entire people of Israel derive and for whom they are named. How is one to reconcile this tension? This dissertation investigates the phenomenon of divine deception in the Jacob cycle (Gen 25-35). The primary thesis is that YHWH both uses and engages in deception for the perpetuation of the ancestral promise (Gen 12:1-3), giving rise to what Anderson has dubbed a theology of deception. Through a literary hermeneutic, emphasizing the symbiotic relationship between both how the text means and what the text means, with theological aims, this study examines the various manifestations of YHWH as Trickster in the Jacob cycle. Attention is given to how the multiple deceptions evoke, advance, and at times fulfill the ancestral promise. In Gen 25-28 YHWH engages in deception to insure Jacob receives the ancestral promise. Here Jacob is seen cutting his deceptive teeth by extorting the right of the firstborn from Esau and the paternal blessing from Isaac. YHWH, however, also plays the role of Trickster through an utterly ambiguous oracle to Rebekah in Gen 25:23, which drives the human deceptions. At Bethel (Gen 28:10-22) Jacob receives the ancestral promise from YHWH, in effect corroborating the earlier deceptions. In Gen 29-31 YHWH uses the many deceptions perpetrated between Jacob and Laban to advance the ancestral promise in the areas of progeny, blessing to the nations, and land. Lastly, in Gen 32-35 YHWH participates in Jacob's final deception of Esau (Gen 33:1-17) through two encounters Jacob has, first with the "messengers of God" and second with God. Jacob's tricking of Esau during their reconciliation results in Jacob's return to the promised land. Can anyone out-trick the Divine Trickster? Anderson thus rightly gives due attention to the Old Testament's image of God as dynamic, subversive, and unsettling, appreciating the complex and intricate ways that YHWH interacts with his people. This witness to YHWH's engagement in deception stands alongside and informs the biblical portrait of YHWH as trustworthy and a God who does not lie
Introduction -- A trickster oracle : reading Jacob and Esau between Beten and Bethel (Genesis 25-28) -- Divine deception and incipient fulfillment of the ancestral promise (Genesis 29-31) -- Replaying the fool : Esau versus YHWH and Jacob (Genesis 32-35) -- Concluding remarks and prospects for further study.
Includes bibliographical references (p. 189-201) and indexes
Revised version of the author's thesis (Ph.D.)--Baylor University, 2010. - Includes bibliographical references (p. 189-201) and indexes
Teilw. zugl.: Waco, Tex., Baylor Univ., Diss., 2010
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jacob -- (Biblical patriarch); Bible -- Criticism, interpretation, etc; Truthfulness and falsehood -- Religious aspects -- Judaism; God (Judaism) -- Attributes; Deception in the Bible; Election (Theology); Hochschulschrift